CHARACTERIZATION OF W198F AND H141Q ?-AMYLASE RECOMBINANT MUTANT FROM BACILLUS MEGATERIUM NL3 WITH RAW STARCH ACTIVITY TEST AND BIOINFORMATICS ANALYSIS - Pramudya, Reivaldi
Starch is a source of carbohydrates for the human body. Starch is produced from photosynthesis which is stored for a long time. Starch-producing crops such as rice, corn and potatoes have been widely cultivated by humans. Currently, starch is widely used in industries such as the food, textile, pharmaceutical and paper industries. Starch is generally degraded into oligosaccharides which can then be utilized according to their needs. Due to its semicrystalline nature, starch granules must be broken down to easily hydrolyze them through a heating process called gelatinization. The starch hydrolysis process can be carried out using acid and heating, but many industries have switched to using enzymatic reactions because they are more environmentally friendly, work specifically, and are needed in small amounts.